Antioxidant and Antitumor Activities of Novel Quercetin-Loaded Electrospun Cellulose Acetate/Polyethylene Glycol Fibrous Materials - Nikoleta Stoyanova; Mariya Spasova; Nevena Manolova; Iliya Rashkov; Ani Georgieva; Reneta Toshkova (MDPI AG, 2020)
The aim of present study was to obtain novel fibrous materials based on cellulose derivative and polyethylene glycol loaded with natural biologically active compound quercetin by electrospinning. Several methods including scanning electron microscopy (SEM), IR spectroscopy, X-ray diffraction analysis (XRD), water contact angle measurements, differential scanning calorimetry (DSC), and UV-VIS spectroscopy were utilized to characterize the obtained materials. The incorporation of polyethylene glycol in the fibrous material resulted in increased hydrophilicity and burst release of quercetin from the fibers. Quercetin-containing fibrous mats exhibited high antioxidant activity as estimated by DPPH free radical scavenging method. In vitro tests with HeLa tumor cells and SH-4 melanoma skin cells were performed in order to determine the cytotoxicity of the novel materials. It was found that the fibrous CA/PEG/QUE materials exhibited high cytotoxic effect against both cell lines. Therefore, the novel polymeric materials containing quercetin are promising candidates for biomedical and pharmaceutical applications.